PENGARUH LUAS LAHAN TEH DAN PRODUKTIFITAS TEH TERHADAP EKPORTEH DI INDONESIA TAHUN 1985 SAMPAI 2019 - suza agustia pratiwi; Devi Andriyani (LPPM Universitas Malikussaleh – Indonesia, 2021)
This study aims to analyze the effect of tea area and tea productivity on tea exports in Indonesia in the 1985-2019 period. The data used in this study are secondary data for the 1985-2019 period. This research model uses multiple linear regression. Research Results Partially the area of tea land has an effect on tea exports in Indonesia. Partially tea productivity has no effect on tea exports in Indonesia. Simultaneously, land area and tea productivity have a positive effect on tea exports in Indonesia